Genetic evidence of gene flow from Indians to Malays. - Teng, Yao Sheng; Tan, Soon Guan (Springer-Verlag, 1979)
Indians appeared in Malaysia early in its history. Sustained contacts often resulted in racial admixture. We have analyzed the biochemical genetic markers phosphohexose isomerase (PHI), lactate dehydrogenase (LDH), adenylate kinase (AK), hemoglobin, rhesus blood group and haptoglobin (Hp) among Malays (the indigenous people of Peninsula Malaysia) and Indians to provide genetic evidence for racial admixture of these two groups. The occurrence of specific rare variants PHI 3-1, LDH Calcutta-1 and Madras-1, and Hb S, as well as the gene frequencies of adenylate kinase and haptoglobin in Malays and Indians confirm the gene flow from Indians to Malays.